Down, out, and under arrest: policing and everyday life in Skid Row - Stuart, Forrest (The University of Chicago Press, 2016)
Fixing the poor -- The rise of therapeutic policing -- From rabble management to recovery management -- Becoming copwise -- Training for survival -- Cooling off the block -- Policing the police